Glycolipid GD3 and GD3 synthase are key drivers for glioblastoma stem cells and tumorigenicity - Yeh, Shih-Chi; Wang, Pao-Yuan; Lou, Yi-Wei; Khoo, Kay-Hooi; Hsiao, Michael; Hsu, Tsui-Ling; Wong, Chi-Huey (Proceedings of the National Academy of Sciences - PNAS, 2016)
The cancer stem cells (CSCs) of glioblastoma multiforme (GBM), a grade IV astrocytoma, have been enriched by the expressed marker CD133. However, recent studies have shown that CD133⁻ cells also possess tumor-initiating potential. By analysis of gangliosides on various cells, we show that ganglioside D3 (GD3) is overexpressed on eight neurospheres and tumor cells; in combination with CD133, the sorted cells exhibit a higher expression of stemness genes and self-renewal potential; and as few as six cells will form neurospheres and 20–30 cells will grow tumor in mice. Furthermore, GD3 synthase (GD3S) is increased in neurospheres and human GBM tissues, but not in normal brain tissues, and suppression of GD3S results in decreased GBM stem cell (GSC)-associated properties. In addition, a GD3 antibody is shown to induce complement-dependent cytotoxicity against cells expressing GD3 and inhibition of GBM tumor growth in vivo. Our results demonstrate that GD3 and GD3S are highly expressed in GSCs, play a key role in glioblastoma tumorigenicity, and are potential therapeutic targets against GBM.